Hot, hungry, or dead - Vallance, Kristina (2015)
Besides habitat loss and fragmentation, global warming is a major anthropogenic factor affecting species today. With temperatures rising, and barriers to movement increasing, many species are turning to behavioural responses deal with increased temperatures. These behavioural responses can be with respect to time or space use. However, with respect to such behavioural responses, animals have to manage the trade-off between food availability, predation risk and temperature. In this study I will look at how differently-sized herbivores respond to variation in temperature and predation risk while keeping food availability constant by using only grazing lawns in Hluhluwe-iMfolozi Park (HiP), South Africa. Camera traps and temperature sensors were used to monitor visitation and temperature on twenty-two grazing lawns across the park. Visibility analysis was also conducted to serve as a measure of horizontal cover or perceived predation risk. It was found that large bodied individuals, white rhino (Ceratotherium simum), were effected by temperature and responded temporally, where as small bodied individuals, impala (Aepyceros melampus), were effected by both temperature and predation risk with both a temporal and spatial response.